A Comparison between Word Tree Branch Method and Interactive Word Wall to Improve Student's Vocabulary - Purnamasari, Ribka; Katemba, Caroline Victorine; Panjaitan, Nelson B. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
The purpose of this study is to find out the improvement of students’ vocabulary between those who were taught through WTB (Word Tree Branch) or IWW (Interactive Word Wall). This study used quantitative research method and comparative design by using pre-test and post-test. This study was designed to find out the answer to the following question: Is there any significant difference on the students’ vocabulary improvement between those who were taught through Word Tree Branch method and those who were taught through Interactive Word Wall method? The sample of this study are, two classes in grade VIII of SMPN 1 Parongpong, Bandung. They were divided into two classes, grade VIII H experienced Interactive word Wall and grade VIII J experienced Word Tree Branch. The instrument used for this study is vocabulary test, which contain 40 questions. The result of this study shows that the students who acquire WTB or IWW method were improved for their vocabulary, vocabulary categorized as “moderate” but there is no significant difference between those two groups of students vocabulary improvement. Keywords: WTB (Word Tree Branch) and IWW (Interactive Word Wall)